A Bibliometric Analysis Of Articles On Settlement In Scopus From 2000 To 2021 Using Social Network Analysis - Riki Satia Muharam; Budiman Rusli; Heru Nurasa; Entang Adhy Muhtar; Nina Karlina; Candradewini Candradewini (Aliansi, 2022)
The aim of this study was to analyse the bibliographic characteristics and content of articles on settlement published in journals indexed by Scopus written by researchers from throughout the world from 2000 to 2021. We conducted a bibliometric and content analysis of publication in the Scopus database. We only retrieved articles written in English. We conducted content analysis using the VOSviewer software and visualized the co-occurrence of keywords and bibliographic coupling of sources and countries. Following the study protocol, we found 2200 articles on settlement over the past 22 years. The most productive journal that published these articles was Journal of Experimental Marine Biology and Ecology (n = 92). The post productive country were the United Kingdom (n = 671), respectively. Based on cititations, the most influential authors, and journals were C. Small (n = 869), and Journal of Coastal Research (n = 1768), respectively. The keywords of research on settlement formed 8 clusters (e.g model, human settlement, structure, poverty, rural settlement, and urbanization). From a global perspective, settlement research in the past two decades has increased significantly. There were European published journals ominated publications. Thus, Asian country need to conduct more active research on this topic.